Entrepreneurial Success Examined through Social Capital and Entrepreneurial Competence among MSME Operators in the PTB Tourist Attraction in Maros City - Irwan Abdullah; Firdaus, Ahmad; Nur Sandi Marsuni; Kahar (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
One area in South Sulawesi Province, precisely in the capital city of Maros Regency, has a downtown tourist attraction known as